Regenerated Type-IIa Fibre Bragg Grating from a Ge–B codoped fibre via thermal activation - Cheong, Y.K.; Chong, W.Y.; Chong, S.S.; Lim, K.S.; Ahmad, Harith (Elsevier, 2014)
A Type-IIa Regenerated Fibre Bragg Grating (RFBG) was fabricated via a thermal activation process at 600 °C, from a saturated type-I Hydrogenated (Type-IH) seed grating, inscribed in a germanium–boron codoped (Ge–B) fibre. Rarely, dynamics of the induced index change featured a negative index grating, wherein blueshifts of Bragg wavelength were observed during a thermal regeneration process. The Type-IIa RFBG has been tested and verified to be temperature stable upon two different sensing temperature ranges, which are 100–600 °C and 600–1000 °C, separately. For the low temperature range, the RFBG showed no significant hysteresis and demonstrated an excellent repeatability, however, with non-linear temperature responses. For the high temperature range, the RFBG showed linear temperature responses with negligible fluctuations in grating stability. The simple regenerative mechanism opens up a new possibility of realizing low cost and yet highly reproducible and reliable grating-based sensors.